Community level barriers for cervical cancer screening in marginalized population - Vora, Kranti; Saiyed, Shahin; Joshi, Rajendra; Natesan, Senthil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In India, cervical cancer is the second common cause of cancer deaths among women of reproductive age, with 469 million Indian women at risk. High risk human papillomavirus genotypes mainly 16 and 18 account of cervical cancer. The burden of cervical cancer can be reduced by regular screening of human papillomavirus (HPV). There is no specific national program for cervical cancer screening. Eligible women have limited knowledge of screening and also limited access to preventive screenings. Methods: The study was conducted in the slum areas of Ahmedabad city in Gujarat. 1088 women between 30-45 years of age were recruited in the study and 536 women consented to give cervical samples for DNA based HPV testing. We collected information regarding knowledge and practice for cervical cancer and HPV along with demographic data. Results: Lack of knowledge and practices around cervical cancer and screening among community women was found. There is a lack of awareness about the importance of preventive healthcare and near absence of evidence-based practices. Sociodemographic characteristics are important predictors of participation in the screening program. Conclusions: In the Indian context, HPV testing is a cost-effective option to prevent cervical cancer. The burden of cervical cancer is incredibly high. With increased ability to accurately detect, population level HPV testing would reduce the burden of cervical cancer and the ultimate cost per person would be minimal, due to the country’s large population. There is a need to develop policy to ensure participation of women in the HPV based cervical cancer screening programs.